Are ultrasound and magnetic resonance imaging of value in assessment of Achilles tendon disorders? A two year prospective study. Issue 2 (1st April 2003) - Khan, K M; Forster, B B; Robinson, J; Cheong, Y; Louis, L; Maclean, L; Taunton, J E
Abstract : Objectives: To ( a ) compare ultrasound (US; including grey scale and colour and power Doppler) and magnetic resonance imaging (MRI; with high resolution and fat saturation sequences) with a clinical yardstick in the evaluation of chronic Achilles tendinopathy, and ( b ) examine whether either imaging method predicted 12 and 24 month clinical outcome. Methods: Forty five patients with symptoms in 57 Achilles tendons were diagnosed with tendinopathy by an experienced sports medicine doctor. All patients underwent US examination (12 MHz probe) with colour and power Doppler, and 25 consecutive patients also underwent MRI with high resolution T1 weighted and STIR sequences. Results: US identified abnormal morphology in 37 of the 57 symptomatic tendons (65%) and normal morphology in 19 of 28 asymptomatic tendons (68%). Baseline US findings did not predict 12 month clinical outcome. The addition of colour and power Doppler did not improve the diagnostic performance of US. MRI identified abnormal morphology in 19 of 34 symptomatic tendons (56%) and normal morphology in 15 of 16 asymptomatic tendons (94%). Lesser grades of MR signal abnormality at baseline were associated with better clinical status at 12 month follow up. Conclusions: US and MRI show only moderate correlation with clinical assessment of chronic Achilles tendinopathy. Graded MRI appearance was associated with clinical outcome but US was not.